Penterjemahan Leksis Kreatif Dalam Sastera Kanak-kanak Terpilih Daripada Bahasa Inggeris Kepada Bahasa Melayu: Satu Kajian Korpus - Zabir, Atikah (2021)
Creative lexis are new words coined and used exclusively by literary authors in their own work. Therefore, creative lexis represents an author’s literary style and identity. In children’s literature, the formation of creative lexis is often phonologically motivated to entertain and enrich children’s reading experience. In addition, discovery of creative lexis also trains child readers to employ effective cognitive strategies when dealing with new words found in academic and non-fiction texts. However, it is difficult to re-create unique elements including creative lexis in translation. As such, there is a tendency to replace unique elements in source texts with typical words in target texts. There are also tendencies for the opposite to happen, whereby unique elements from the source texts are retained in their original forms in the target texts. Both tendencies can be explained using the Laws of Translation hypothesis which states that unique elements are reduced or highlighted in translation, depending on not only cognitive but also various contextual factors. Based on reviews of previous studies, there is a need to study creative lexis and its translation into Malay because there are very limited information especially empirical data on Malay translations of children’s books despite translation playing a crucial role in the Malaysian children’s books industry. Therefore, this study is carried out to fulfil three main objectives